NATIONAL SIGNS AS A CULTURAL RESOURCE OF ETHNIC TOURISM DEVELOPMENT - S. N. Fedorova (Концепт: философия, религия, культура, 2019)
Signs ingrained in our everyday lives have already become an integral part of our nature, although insufficiently perceived yet. The purpose of the paper is the research of signs in modern life, in particular, in tourists’ lives. The scientific review of definitions “sign”, “ethnic tourism” is presented. National signs are predictions checked by time, based on an assumption of peoples’  communication with natural phenomena, various properties of objects and events which happen to them, expressed in a short, figurative form. The national sign passes from generation to generation. Signs form behavior stereotypes in ordinary situations, promote thinking dogmatization as a certain defense mechanism preserving cultural tradition from external influence; maintain separate mythological ideas about interdependence of the nature and society.In this article national signs of Yakuts and Evenks which reflect their culture, traditions and customs are considered. Studying signs gives tourists a chance to get acquainted not only with nature, but also with original culture; to make comparisons of national characters, mentality and archetypes. Tours oriented to learning foreign traditions and customs gain more popularity nowadays. As a result ethnocultural tourism aimed at studying socio-cultural and traditional patterns, including signs, reflect the way of life of people living in extreme conditions, as well as their environmental friendliness, in the best way possible. The author concludes that preservation and revival of national signs is critical for tourists’ acquisition and the development of ethnic tourism.